Digital Technology Capability and Inclusive Development: The Mediating Role of Digital Resilience and the Moderating Role of Institutional Support - Resanti Lestari (Journal of Advanced Research in Social Sciences and Humanities, 2026)
Aim: This study investigates how digital technology capability contributes to inclusive development outcomes through the mediating role of digital resilience, while examining the moderating influence of institutional support. It aims to provide a deeper understanding of how technology-driven transformation can be translated into equitable societal progress in emerging digital economies.Methodology: A quantitative, cross-sectional, and explanatory research design was employed. Data were collected from 215 professionals representing digital startups, SMEs, local government digital programs, and community innovation organizations across Indonesia using a structured five-point Likert scale questionnaire. Stratified random sampling ensured representation across urban, semi-urban, and rural regions. The proposed moderated mediation model was tested using ADANCO 2.3 with PLS-SEM techniques.Findings: Results confirm that digital technology capability has a direct and significant effect on both digital resilience and inclusive development outcomes. Digital resilience was found to mediate this relationship, demonstrating its central role in translating capability into societal impact. Institutional support significantly strengthened the effect of technological capability on resilience and enhanced the indirect impact on inclusive development.Implications/Novel Contribution: This study uniquely integrates digital capability, resilience, and institutional governance into a unified framework, offering policymakers and digital strategists a strategic pathway for designing resilience-centered, institution-driven digital transformation for inclusive national development.